Pelatihan Penciptaan Syair Meudike Berorientasi Nilai Religius dan Sosial pada Generasi Muda - Samsuri Samsuri; Yuli Astuti; Ilham Septian (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This community service activity aimed to improve young people’s understanding of the traditional art of Meudike while instilling religious and social values through Meudike poetry creation training at SMP Negeri 3 Ingin Jaya, Aceh Besar Regency. The activity was conducted using a Problem Based Learning (PBL) approach combined with creative learning based on traditional arts. The participants consisted of 30 tenth-grade students who were involved in several stages of activities, including presenting problems related to juvenile delinquency, problem-solving discussions, creating Meudike poetry, determining melodies, and presenting the works in groups. The results showed that the training was able to enhance students’ creativity, critical thinking skills, collaboration, communication, and appreciation of Acehnese local culture. The poetry created by the students contained moral messages as well as religious and social values related to everyday life. In addition, this activity also served as a medium for character building through the internalization of religious and social values in cultural arts learning. Therefore, Meudike poetry creation training can become one of the efforts to preserve Acehnese traditional arts while also serving as a means of character education for the younger generation.